(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines the conquest and liquidation of the Kokand Khanate by the Russian Empire based on information from the pages of the newspaper of the Turkestan region. The newspaper periodically (in chronological order) outlines such issues as the relations of the Turkestan Governor-General with the Kokand Khanate, the loss of a significant territory by the khanate as a result of the uprising that began in Kokand, and then the final liquidation of the khanate and the creation of the Ferghana region in its place, the fate of the former khans and leaders of the uprising, as well as the consequences of the invasion